Nonlinear Controller Design for Series-Compensated DFIG-Based Wind Farms to Mitigate Subsynchronous Control Interaction - Chowdhury, Md. Ayaz; Mahmud, Md. Apel; Shen, Weixiang; Pota, Hemanshu Roy (IEEE transactions on energy conversion, 2017)
This paper proposes a nonlinear controller to mitigate subsynchronous control interaction (SSCI) in series-compensated doubly fed induction generator (DFIG)-based wind farms. The controller is designed based on partial feedback linearization (PFL) and the proposed design approach involves scrutinizing the partial feedback linearizability of the system. The stability of the internal dynamics, which is not transformed into linear autonomous subsystems by PFL, is also analyzed in the process of deriving the control laws. The frequency scanning method is used to evaluate the performance of the proposed PFL controller, and the performance is compared to that of a finely tuned conventional proportional integral controller. A grid-connected series-compensated 100-MW DFIG-based offshore wind farm is used to demonstrate the performance of the proposed scheme through the identification and mitigation of subsynchronous resonance. An analysis of the power system reveals that the resistance is negative across the entire subsynchronous frequency range, while the reactance becomes negative around 42 Hz. The proposed controller effectively mitigates SSCI, and it can be observed that it results in positive resistance and reactance values across the entire subsynchronous frequency range. Results from the eigenvalue (modal) analysis and electromagnetic transient simulation also confirm the results obtained from frequency scanning.